The age-period cohort problem: Set identification and point identification - Martin Browning; Ian Crawford; Marike Knoef (Centre for Microdata Methods and Practice (cemmap), 2012)
Various methods have been used to overcome the point identification problem inherent in the linear age-period-cohort model. This paper presents a set-identification result for the model and then considers the use of the maximum-entropy principle as a vehicle for achieving point identification. We present two substantive applications (US female mortality data and UK female labor force participation) and compare the results from our approach to some of the solutions in the literature.
Keywords: 330